The creation and administrative divisions of Łódź Voivodeship - Jakóbczyk-Gryszkiewicz, Jolanta (Acta Geographica Lodziensia, 2019)
The purpose of the author was to present the origin and evolution of the Łódź Voivodeship, created in 1919. Łódź, founded in the 15th century, was a small agricultural town. It grew rapidly in the 19th century when it turned into a major centre of the textile industry. The intensive development of industry and the growth of the population up to 315,000 (in 1897) were not matched by the development of appropriately scaled services nor by adequate administrative functions. The newly created (in 1919) Łódź Voivodeship was made up of adjacent administrative units from the neighbouring voivodeships of Warsaw, Poznań and Kielce. It first comprised 13 counties (poviats), and, from 1938, only eight counties. During the hundred years of its existence, the area of this voivodeship has changed several times – it was the largest in 1939 (20,400 km2) and smallest in the period of 1975–1999 (1,500 km2). Presently (2017), the Łódź Voivodeship covers 18,200 km2. It is divided into 177 com-munes (gmina), 21 counties and three urban counties. There are 44 cities and towns and a population of 2.5 million. Its urba- nisation index is 64%. The population of Łódź city dropped to 690,000 in 2017.